Glorify the Lord Ensemble’s Existence and Strategy in the Indonesian Music Industry - Nida Ulhanifah Setiadi; Ignasius Herry Subiantoro; Indra Ridwan (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2024)
Indonesia’s music industry has undergone a significant transformation from the vinyl disc era to the digital era, with new challenges and opportunities in maintaining the existence of music groups. This research aims to explore Glorify the Lord Ensemble’s journey in gaining attention in the music industry and analyse their strategies for long-term sustainability. Qualitative research methods were used, including observation, interviews, and documentation studies to collect data from rehearsals, performances, and internal group interactions. The results revealed that Glorify’s initial appeal came from their founder, Daud PM Saba, who blended pop, rock, R&B soul, and black gospel genres with signature choreography, attracting the attention of renowned artists and fans. Their sustainability strategy involves regular activities for members and active publications on social media, maintaining their existence during the passing pandemic and in the midst of music industry competition. Recommendations from this research are to continue adapting innovations in content, and social media interactions, as well as maintaining the quality of rehearsals, and collaborations that strengthen their reputation. This research provides important insights into successful existence strategies in the competitive music industry.